Teacher Empowerment in the Development of Artificial Intelligence (AI)-Based Learning Media in Meranjat Village Ogan Ilir Regency - Chotimah, Umi; Waluyati, Sri Artati; Camellia; Maharani, Rizki; Alipraja, Muhammad; Erlande, Rike; Amziyah, Dini; Valentin, Della; Rosadi, Yudisia Sofani Putra; Naila, Siti; Patricia, Putri (Unram Journal of Community Service, 2025)
Training on the use of Artificial Intelligence-based learning media was held as part of teacher empowerment activities in developing such media. This community service activity was held by the Civic Education Study Program, Faculty of Teacher Training and Education, Sriwijaya University. The Community Service Team trained teachers at SMPN 1 Indralaya Selatan, Meranjat Village, Ogan Ilir Regency, to develop Artificial Intelligence (AI)-based learning media. This training and mentoring aimed to improve teachers' capabilities so they could create innovative and effective learning. The methods applied included counseling, training, and mentoring in direct practice using Artificial Intelligence-based media from Wayground AI, Canva AI, Avatar AI, Renderforest AI, LMS AI, and ChatGPT AI, as well as assessments through pretests and posttests to measure the increase in participants' understanding. The results showed a significant increase in understanding of creating Artificial Intelligence-based learning media, with the average post-test score of participants increasing from 37.7 to 80.03 from a total of 30 participants. The evaluation results showed high satisfaction from participants with the material provided and its relevance to needs in the field. The participants' response was very positive, as evidenced by their active discussions, willingness to experiment with the media, and commitment to creating learning products. The program is planned to continue with follow-up publications in newspapers, YouTube, and journals, as well as evaluation meetings and activity reports. It is hoped that this program will continue to empower teachers to improve and develop AI-based learning media in schools.